Development of an Innovative Career Development Program for Early-Career Women Faculty - Suzanne C Danhauer PhD; Janet A Tooze PhD; Natalie AM Barrett; Jamie S Blalock MA; Carol A Shively PhD; Mary Lou Voytko PhD; Sonia J Crandall PhD (SAGE Publishing, 2019)
Objective Our institutional Women in Medicine & Science Program (formerly the Office of Women in Medicine and Science) developed the Early Career Development Program for Women to promote the careers of women faculty. At 6 monthly sessions, participants learn relevant content (imposter syndrome, strengths, change style, career management, assertive communication, feedback, personal influence, conflict management, negotiation, importance of mentors, resilience, and self-care); exchange ideas; and expand their professional networks. Here, we report changes in participants' career skills/knowledge, confidence, and perceptions of the current environment after attending the program. Method Between 2014 and 2017, participants (N = 65) completed pre- and post-program surveys that assessed career knowledge and skills, confidence, and perceptions of the current environment and provided program feedback. Results Most skills showed pre-post significant improvement. The greatest increases occurred in knowing paths to promotion, tailoring communication style, ability to manage conflict, and ability to handle personal-professional role balance. Women reported a significant increase for all items measuring confidence. Among these items, establishing networks, understanding institutional culture, providing feedback, motivating others, strategic planning, delegating, and conflict management had the largest increases. Overall, 89.3% of respondents rated the program impact as very strong/profound, 98.5% rated the concepts as essential, 95.2% rated the skills as essential, and 90.8% rated the sense of community with women in their class as very/extremely close. Conclusions Work-related skills/knowledge, confidence, and perceptions of the current environment increased significantly among program participants. These early-career women faculty indicated that the program augmented the skills needed to develop their careers in an academic medical center.